Knowledge Sharing Implications of the Emergence of GPT Chat on Learning Methods at SMP 4 Muhammadiyah Depok, West Java - Laode Muhamad Fathun; Chiara Vincha; Aisha Saharani; Algis Zalita Pitra (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
This presentation  aims to describe the  activities of the  Community Partnership Program or PKM carried out at SMP 4Muhammadiyah Depok, West Java.   This activity took the  topic of the Contribution and implications of Chat GPT to learning methods in the digital era.    This activity is carried out by socialization, discussion and practice methods. The result  obtained was that Chat GPT turned out to greatly influence the learning method at SMP 4 Muhammadiyah Depok. Teachers   worry about  their students not using technology wisely.  To overcome these  problems, our  team provides hands-on  practice  in the responsible  and plagiarism-free use of GPT Chat.   In addition, we also provide the  practice of  making power points to  teachers so that  the material provided to students can be more interesting in learning. GPT chat has both positive and negative  impacts depending on how humans use it.